Evaluation of the Radiopacity of Esthetic Root Canal Posts - Rodrigues, Eliana; Salzedas, Leda Maria Pescinini [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Pedrini, Denise [UNESP] (Wiley-Blackwell, 2014)
The radiopacity of esthetic root canal posts may impair the assessment of their fit to the root canal when using radiographic images. This study determined in vitro the radiographic density of esthetic root canal posts using digital images. Thirty-six roots of human maxillary canines were assigned to six groups (N = 6 per group): Reforpost (RP); Aestheti-Plus (AP); Reforpost MIX (RPM); D.T. Light Post (LP); Reforpost Radiopaque (RPR); and White Post DC (WP). Standardized digital images of the posts were obtained in different conditions: outside the root canal, inside the canal before and after cementation using luting material, and with a tissue simulator. Analysis of variance was used to compare the radiopacity mean values among the posts outside the root canal and among the posts under the other conditions, and the t unpaired test to compare the radiopacity between the posts and the dentin, and between the posts and the root canal space. There was no statistically significant difference in radiopacity between RP and RPM, and LP and WP. AP posts showed radiopacity values significantly lower than those for dentin. No statistically significant difference was found between posts (RP and AP) and the root canal space. A statistically significant difference was observed between the luted and non-luted posts; additionally, luted posts with and without tissue simulator showed no significant differences. Most of the cement-luted posts analyzed in this study were distinguishable from the density of adjacent dentin surfaces, allowing radiographic confirmation of the fit of the post in the canal.Clinical SignificanceThe success of using esthetic root canal posts depends mainly on the fit of the post within the canal.[1] The radiopacity of a post allows for radiographic imaging to be used to determine the fit, an important factor in a clinical perspective.